Pengaruh Store Atmosphere Terhadap Keputusan Pembelian Pada Pillar Coffe Shop di Pekanbaru - Devli Anas Wati; Annisa Mardatillah (SYNERGY: Jurnal Bisnis dan Manajemen, 2024)
The Research carried out has the aim of finding out the influence of store atmosphere on purchasing decisions at pillar coffee shop in pekanbaru. The type of research carried out uses quantitative methods.The sampling method is accidental sampling by taking a sample of 80 people.the data collection technique that the author uses is the method of observation, interviews and distributing questionnaires. meanwhile,the data analysis technique in this research used SPSS 27, namely validity test,reliability test, simple linear regression analysis test, t test, and coefficient of determination test (R2). So the results of this research prove that the store atmosphere has a positive and significant influence on purchasing decisions. Based on this research, it is recommended that pillar coffee shop continue to maintain the superiority of the store atmosphere that they have,because a goog and comfortable store atmosphere will attract consumers to visit the coffee shop so that it can increase purchases of pillar coffee shop